Prevalence of Cigarette Smoking and Nicotine Dependence in Men and Women Residing in Two Provinces in China - Ma, Yunlong; Wen, Li; Cui, Wenyan; Yuan, Wenji; Yang, Zhongli; Jiang, Keran; Jiang, Xianzhong; Huo, Meijun; Sun, Zilong; Han, Haijun; Su, Kunkai; Yang, Shigui; et al. (Frontiers in Psychiatry, 2017)
Aims: Although it is known that there is a high smoking prevalence among Chinese, key issues such as social and environmental factors impacting smoking initiation and persistence, the percentage of smokers considered nicotine dependent (ND), and the availability and use of ND treatments have rarely been investigated. Methods: To address these issues, from 2012 to 2014, we conducted a large-scale study in the Zhejiang and Shanxi provinces of China using the Fagerström Test for Nicotine Dependence (FTND) and other validated questionnaires. Results: Of the 17,057 subjects, consisting of 13,476 males and 3,581 females aged 15 years or older, the prevalence of male smoking was 66.1% (95% confidence interval [CI] 65.5%, 66.9%) and that of female smoking was 3.2% (95% CI 3.0%, 3.8%). Among males, 25.8% (95% CI 25.0%, 26.5%) were low-to-moderate ND (LM-ND), and 11.8% (95% CI 11.2%, 12.3%) were highly ND (H-ND), persons who have significant difficulty quitting without treatment. The degrees of ND were related to age, extent of education, and annual family income. The social–environmental factors examined conveyed a higher risk for smoking initiation, which is particularly true for the influence of smoking by friends. Furthermore, current smokers had a significantly higher risk of suffering respiratory and digestive symptoms. Conclusions: These data not only show a high smoking prevalence in Chinese men but also reveal that a relatively large number of smokers are highly ND. Considering that few Chinese smokers seek ND treatment, a comprehensive smoking prevention and treatment program designed specifically for Chinese persons is greatly needed.